Designing Character: Kartu Digital Santri as a Triadic Formation Instrument in Pesantren - Taufikin; Moh Solihuddin (Educazione: Journal of Education and Learning, 2026)
Digital financial technology has entered educational institutions primarily as an administrative solution, yet its potential as an instrument of character formation remains largely unexplored, particularly within Islamic boarding school contexts where moral development is a foundational institutional mission. This study aims to identify the character clusters that emerge through daily interaction with the Kartu Digital Santri (a student digital wallet system), to analyse the mechanisms through which values are internalised in practice, and to propose a conceptual model explaining the relationship between digital financial practice and character formation. Employing a qualitative intrinsic case study design, data were collected over four months from 48 participants across three informant groups through participatory observation, in-depth interviews, and document analysis, and were analysed using thematic analysis supported by NVivo software. The findings reveal three interlocking character clusters formed through daily interaction with the system: self-regulation, emerging from balance constraints and spending accountability; moral character, developing as a structural consequence of transaction transparency; and future skills, cultivated through repeated engagement with cashless financial practice. Together, these clusters constitute the Triadic Character Formation model, which demonstrates that habitus, self-regulation, moral internalisation, and adaptive literacy can be simultaneously activated through deliberate system design. The findings carry significant implications for transformational education: they suggest that genuine educational transformation does not require new curricula or additional instruction but a fundamental reconceptualisation of how institutional systems are designed, positioning the architecture of daily practice as the most powerful and underutilised site of learning and character development available to educational institutions.